EFFICIENT BEEF PRODUCTION TECHNOLOGY (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The article highlights the results of scientific and economic experience in studying the growth and development of cattle bulls and the effectiveness of beef production technology.It has been established that the introduction of mineral and vitamin supplements into the diet of imported cattle bulls during cultivation improves the digestibility of nutrients in the feed eaten, increases the formation of meat productivity, daily live weight gain and the efficiency of beef production technology in farm conditions.